PENGARUH RESILIENSI DAN LITERASI DIGITAL TERHADAP ENTREPRENEURIAL READINESS MAHASISWA DI ERA DIGITAL - Mona Yuliana; Elvi Rahmi (MANAJEMEN DEWANTARA, 2025)
This study subjective to analyze the influence of resilience and digital literacy on entrepreneurial readiness of students of the Faculty of Economics and Business, Padang State University in the digital era. With a population of 3,565 students. The sample collection technique used purposive sampling with criteria that have completed entrepreneurship courses and entrepreneurial practices with a sample of 100 respondents and analyzed using SPSS 27. The results of the study indicate that resilience and digital literacy have a positive and significant effect on entrepreneurial readiness. The implications of this study suggest the need for integrated training programs and curriculum development that support both aspects.